The Effect of the Rebozo Technique on Reducing Lower Abdominal Pain in Pregnant Women in the Third Trimester - Aisah Hajirin; Widia Shofa Ilmiah (Jurnal Siti Rufaidah, 2025)
and well-being of pregnant women. This study aims to examine the effect of the Rebozo technique in reducing lower abdominal pain in third-trimester pregnant women. A total of 65 third-trimester pregnant women at UPT Puskesmas Rum Balibunga participated in the study. The results show a significant reduction in pain levels after applying the Rebozo technique, with all participants reporting negative ranks (pain reduction). The Wilcoxon Signed Ranks Test yielded a Z = -8.062 and p-value = 0.000, indicating that the reduction in pain after applying the Rebozo technique was statistically significant. This pain reduction can be attributed to the relaxation effect provided by the Rebozo technique, which helps relieve muscle tension and provide physical support to the pregnant woman's body. The study suggests that the Rebozo technique can be an effective non-pharmacological alternative for reducing pain in pregnant women, especially in the third trimester.